Campylobacter jejuni survival in chicken meat as a function of temperature. - Blankenship, L C (1982)
Recognition of Campylobacter fetus subsp. jejuni (referred to hereafter as C. jejuni) as an important human pathogen and its isolation from meat products indicate the need for knowledge of its survival characteristics in meats. Thermal death times (D-values) for a single strain and a five-strain composite were determined in 1% peptone and autoclaved ground chicken meat at temperatures ranging from 49 to 57 degrees C. Survival was determined for these strains in chicken meat at 4, 23, 37, and 43 degrees C. Survival was also determined on raw chicken drumsticks stored at 4 degrees C in either an ambient or a CO2 atmosphere. D-values were greater in chicken meat than in peptone in all cases. D-values in peptone for strain H-840 at 49, 51, 53, 55, and 57 degrees C were 15.2, 4.90, 1.71, 0,64, and 0.25 min, respectively. The corresponding D-values in ground chicken meat were 20.5, 8.77, 4.85, 2.12, and 0.79 min, respectively. Similar results were obtained with a composite of five strains. When sterile ground chicken meat was inoculated with approximately 10(6) to 10(7) C. jejuni cells per g and stored at 37 degrees C in an ambient atmosphere, a 1-to 2-log count increase occurred during the first 4 days, followed by a gradual decline of about 1 log during the remainder of the 17-day storage period. No growth was observed among similarly inoculated samples that were stored at 4, 23, and 43 degrees C but counts declined by about 1 to 2 logs at 4 degrees C (17 day), by 2.5 to 5 logs at 23 degrees C (17 days), and to undetectable levels at 43 degrees C (between 10 and 16 days). Survival on raw chicken drumsticks stored at 4 degrees C in CO2 and in an ambient atmosphere declined by about 1.5 and 2.0 logs, respectively, during 21 days of storage. The effect of temperature on the survival of C. jejuni in chicken meat was similar to that reported in other natural and laboratory milieus. Ordinary cooking procedures that destroy salmonellae would be expected to destroy C. jejuni.